Composition dependence of tracer diffusion coefficients in Fe–Ga alloys: A case study by a tracer-diffusion couple method. (15th January 2021) - Muralikrishna, G.M.; Tas, B.; Esakkiraja, N.; Esin, V.A.; Kumar, K.C. Hari; Golovin, I.S.; Belova, I.V.; Murch, G.E.; Paul, A.; Divinski, S.V.
Abstract: The problem of estimation of the tracer diffusion coefficients is solved by utlizing a novel radiotracer-diffusion couple technique in the absence of a suitable radioisotope of one of the components and reliable thermodynamic parameters. This is demonstrated by generating reliable and reproducible mobility data in the alloys of the Fe–Ga system with a strong composition dependence of the diffusion coefficients. Tracer- ( 59 Fe) and inter-diffusion are simultaneously measured in three couples Fe/Fe-16 Ga, Fe/Fe-24 Ga and Fe-16 Ga/Fe-24 Ga at 1143 K in at.%). The results obtained for the couples with different end-members are in an excellent agreement with each other for the overlapping composition intervals. The influence of the molar volume on the measured tracer- ( 59 Fe) and inter-diffusion coefficients is evaluated. Using thermodynamic calculations, the Ga tracer diffusion coefficient and the vacancy wind factor are determined via the Darken-Manning relation for the composition range of 0–24 at.% Ga. The results in this study confirm the reliability of the radiotracer-diffusion couple technique for producing highly accurate diffusion data. As a result, this helped for optimizing the mobility description of the bcc phase of the Fe–Ga system. The Ga tracer diffusion coefficients are further estimated via experimental determination of the ratio of the Fe and Ga tracer diffusivities at the Kirkendall marker planes and utilizing the Fe tracer diffusion coefficients measured directly by the radiotracer method. Graphical abstract: Image, graphical abstract